More than sleep and wake disturbances: An actigraphic study showing the sleep-wake pattern dysregulation in epilepsy. (January 2022) - Liguori, Claudio; Spanetta, Matteo; Fernandes, Mariana; Izzi, Francesca; Placidi, Fabio; Mercuri, Nicola Biagio
Highlights: Sleep alterations and lower daytime activity were evident in patients with epilepsy. Patients with epilepsy showed poor sleep efficiency and longer sleep latency. An evening chronotype preference was documented in patients with epilepsy. Abstract: Objective: This study aimed to assess the sleep-wake pattern in patients with epilepsy compared to controls. Methods: Patients with epilepsy and controls underwent a 14-day actigraphic recording to evaluate the rest-activity cycle. A sleep medicine interview was performed to exclude conditions interfering with the sleep-wake cycle in both patients and controls. Patients presenting seizures during the actigraphic recording were excluded. Daytime activity, nocturnal sleep, and non-parametric circadian rhythm activity (NPCRA) were analysed. Results: Twenty-two patients (mean age 49.5 ± 19.84 years; 50% female) and 17 controls were included. Patients showed lower sleep efficiency and longer sleep latency than controls. NPCRA analysis showed lower inter-daily stability and higher intra-daily variability in patients, who also presented lower daytime activity and a longer central phase measure (CPM) than controls. Conclusions: Patients showed a significant alteration of the sleep-wake pattern, featured by lower synchronization and higher fragmentation of the rest-activity rhythm. Moreover, patients showed a delayed CPM compared with controls, corresponding to an evening chronotype tendency. Nocturnal sleep alteration and lower daytime activity were also evident. Therefore, patients with epilepsy present an alteration of the sleep-wake pattern and clinicians should increase their awareness about circadian rhythmicity dysregulation in epilepsy.